Site-saturation Mutagenesis is more Efficient than DNA Shuffling for the Directed Evolution of β-Fucosidase from β-Galactosidase - Parikh, Monal R. (2005)
Protein engineers use a variety of mutagenic strategies to adapt enzymes to novel substrates. Directed evolution techniques (random mutagenesis and high-throughput screening) offer a systematic approach to the management of protein complexity. This sub-discipline was galvanized by the invention of DNA shuffling, a procedure that randomly recombines point mutations in vitro. In one influential study, Escherichia coli β-galactosidase (BGAL) variants with enhanced β-fucosidase activity (tenfold increase in k(cat)/K(M) in reactions with the novel para-nitrophenyl-β-d-fucopyranoside substrate; 39-fold decrease in reactivity with the “native” para-nitrophenyl-β-d-galactopyranoside substrate) were evolved in seven rounds of DNA shuffling and screening. Here, we show that a single round of site-saturation mutagenesis and screening enabled the identification of β-fucosidases that are significantly more active (180-fold increase in k(cat)/K(M) in reactions with the novel substrate) and specific (700,000-fold inversion of specificity) than the best variants in the previous study. Site-saturation mutagenesis thus proved faster, less resource-intensive and more effective than DNA shuffling for this particular evolutionary pathway.